Morphological Characters of Early Harvest Age Mutant Selection M3 Generation of Black Rice (Oryza sativa L.) Irradiated by Gamma Ray - Nandariyah - Nandariyah; Parjanto Parjanto; Sutarno Sutarno; Riyatun Riyatun; Rifqi Syarif Muhammad (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
Black rice contains higher levels of anthocyanin, fiber, and protein compared to local white rice. The price of black rice is higher compared to local white rice, it is one of prove that black rice has functional and economical values. The main obstacles in the cultivation of black rice are the long harvest age, high plant height, and lack of productivity. One way that can be applied to overcome this dissadvantageis with the utilization of gamma ray irradiation. The purpose of this research is to get the early-season rice, short stem, and higher productivity. This research was conducted in Tempel, Gatak, Sukoharjo District, by planting M3 seed (gamma ray irradiation of 300 Gray dosage on M2). The results of black rice from gamma ray irradiation of 300 gray dosage are M-CI-03-239, M-CI-03-244, M-CI-03-246, M-CI-03-346, M- CI-03-350, M-CI-03-234, M-CI-03-346, M-CI-03-350, M-CI-03-250, M-CI- 03-346, M-CI-03-CI-03-262, M-CI-03-265, M-CI-03-270, M-CI-03-283, and M-CI-03-311 with the agronomical properties of early age, i.e 2 weeks faster (64 days) with control (80 days). There are 125 short-postured plants of gamma ray irradiation result with 99.2% percentage. There are 12 individual plants in the M3 strain (M-CI-03-240, M-CI-03-251, and M-CI-03-261) of gamma ray irradiation with the maturation category, short stems, and high productivity compared with control. The difference of productivity of irradiated crops with control is 57,91%.